Implementing an online pharmaceutical service using design science research - Luís Velez Lapão; Miguel Mira da Silva; João Gregório (BMC Medical Informatics and Decision Making, 2017)
Abstract Background The rising prevalence of chronic diseases is pressing health systems to introduce reforms. Primary healthcare and multidisciplinary models have been suggested as approaches to deal with this challenge, with new roles for nurses and pharmacists being advocated. More recently, implementing healthcare based on information systems and technologies (e.g. eHealth) has been proposed as a way to improve health services. However, implementing online pharmaceutical services, including their adoption by pharmacists and patients, is still an open research question. In this paper we present ePharmacare, a new online pharmaceutical service implemented using Design Science Research. Methods The Design Science Research Methodology (DSRM) was chosen to implement this online service for chronic diseases management. In the paper, DSRM’s different activities are explained, from the definition of the problem to the evaluation of the artifact. During the design and development activities, surveys, observations, focus groups, and eye-tracking glasses were used to validate pharmacists’ and patients’ requirements. During the demonstration and evaluation activities the new service was used with real-world pharmacists and patients. Results The results show the contribution of DSRM in the implementation of online services for pharmacies. We found that pharmacists spend only 50% of their time interacting with patients, uncovering a clear opportunity to implement online pharmaceutical care services. On the other hand, patients that regularly visit the same pharmacy recognize the value in patient follow-up demanding to use channels such as the Internet for their pharmacy interactions. Limitations were identified regarding the high workload of pharmacists, but particularly their lack of know-how and experience in dealing with information systems (IST) for the provision of pharmaceutical services. Conclusions This paper summarizes a research project in which an online pharmaceutical service was proposed, designed, developed, demonstrated and evaluated using DSRM. The main barriers for pharmacists’ adoption of online pharmaceutical services provision were the lack of time, time management and information systems usage skills, as well as a precise role definition within pharmacies. These problems can be addressed with proper training and services reorganization, two proposals to be investigated in future works.